A comparative analysis on cranial ontogeny of South American fur seals (Otariidae: Arctocephalus) - Tarnawski, Bárbara Alejandra; Flores, David Alfredo; Cassini, Guillermo Hernán; Cappozzo, Humberto Luis (Zoological Journal of the Linnean Society)
We analysed the cranial ontogeny of male Arctocephalus australis (Zimmermann, 1783) (N=116), Arctocephalus gazella (Peters, 1875) (N=69), and Arctocephalus tropicalis (Gray, 1872) (N=51) to study skull growth and its allometric patterns in the genus. We used 15 metric variables with bivariate and multivariate approaches to detect interspecific similarities and differences between growth trends, which we discussed in the context of phylogeny and life history. We found common trajectories in 20% of variables, detecting that the differences between adults were associated with size. We detected higher growth rates in A.gazella than in A.australis and A.tropicalis, which were associated with shape differences. Amongst the three species, A.tropicalis was morphologically intermediate, showing additional common trends with A.gazella and A.australis, and an intermediate position in the multivariate morphospace. Allometric patterns were also compared with growth trends described for Otaria byronia (Péron, 1816) and Mirounga leonina (Linnaeus, 1758). We detected positive allometry in Arctocephalus for the mastoid width (MW) but negative allometry in O.byronia and M.leonina. This could indicate that males of Arctocephalus exhibited a delayed development of MW. Finally, the presence of common growth trends for the skull length and the postorbital constriction could indicate a conservative pattern within otariids. Fil: Tarnawski, Bárbara Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Flores, David Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Cassini, Guillermo Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de ...